2016
DOI: 10.1055/s-0036-1592110
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Lung Cancer: A Review

Abstract: Lung cancer patients are at high risk of suffering due to severe and refractory symptoms, concomitant respiratory comorbidity, frequent disease progression, and treatment that can worsen and compromise quality of life. Palliative care (PC) has shown multiple benefits to cancer patients such as better quality of life, higher patient and family satisfaction, improved disease understanding, less symptom burden, fewer depressive symptoms, less aggressive end of life care, and even improved survival with early impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 100 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…Meanwhile, other studies have shown that patients with lung cancer have the greatest use of palliative care, likely because of their high risk of illness. 4,5 Thus, data have been heterogeneous, and larger studies such as ours are warranted, especially from claims-based databases such as Medicare or private insurance plans. Finally, we found that patients with more advanced cancer stage and grade had higher odds of receiving palliative care compared to patients with less advanced stages and grades for all durations of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, other studies have shown that patients with lung cancer have the greatest use of palliative care, likely because of their high risk of illness. 4,5 Thus, data have been heterogeneous, and larger studies such as ours are warranted, especially from claims-based databases such as Medicare or private insurance plans. Finally, we found that patients with more advanced cancer stage and grade had higher odds of receiving palliative care compared to patients with less advanced stages and grades for all durations of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Palliative care has been increasingly recognized as an important part of cancer care 3,4 but remains underutilized and often is provided too near end of life (EOL). 5,6 There is a definite gap in knowledge regarding why palliative care is underutilized in cancer care despite its benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Typically, PC is not sought until the disease is at an advanced stage requiring hospitalization or if the patient has uncontrolled symptoms that severely impair their QOL. 27,28 Previous studies have suggested that late referrals to PC are inadequate to alter the quality and delivery of care provided to patients with cancer; thus, several organizations such as the ASCO, National Comprehensive Cancer Network, and European Society of Medical Oncology have issued clinical opinions recommending the use of PC earlier in the course of disease. 19,[29][30][31][32] The importance of early PC and the impetus for the development of these guidelines have been provided by several randomized trials that have provided evidence that patients who received early PC input had improved QOL, reduced intensive care unit admissions, increased time spent at home, longer stay in hospice, and lower overall cost of care and health-care use.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Among patients with colorectal cancer for whom a cure is not achievable (ie, about 80% of all patients with metastatic disease), 7,8 palliative care is reported to be associated with improved patient survival and quality of life. 4,[9][10][11][12] Palliative care has also been reported to decrease the need for expensive acute hospital care in the last few months of life and to decrease the cost of end-of-life care among patients with advanced cancer. [13][14][15][16][17] However, the benefits of palliative care interventions are not exclusive to patients with stage IV colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%